REHABILITATE AND RESTORE THE IMAGE OF NEIGHBORHOODS DEGRADED BY URBAN IMPROVEMENT OPERATIONS IN THE "WEST-PLAIN" CITY OF ANNABA. What place for the citizen in the implementation of this policy ? (Sciences & Technologie. D, Sciences de la terre, 2019)
This article aims to assess the policy of urban improvement characterizing some neighborhoods of the city of Annaba. A program to upgrade its urban fabric has scored for the year 2010, sixty-two operations for urban improvement including 27 relating to collective habitat. These operations combine all the aspects concerning the rehabilitation of the image of the infra-urban territories by the servicing and the development of their urban spaces. The operations of urban improvement contributed to the evolution of the living environment of several districts, but what about their quality of execution? The implication of the civil society constitutes a decisive stage for the success of any project today, if this politics emanates from a plural action, what is its strategy and which are its tools ?